2023
DOI: 10.3390/su15139981
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance of Green Façades: Research Trends Analysis Using a Science Mapping Approach

Abstract: Buildings consume a significant part of the world’s resources and energy. The growing environmental awareness and urgent need to reduce energy consumption have highlighted the importance of introducing innovative solutions as nature-based systems in new buildings’ construction and retrofitting. In this regard, green façades that integrate vegetation into building envelopes are attractive. This paper presents a bibliographic analysis, based on science mapping, of the available literature on green façades from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 138 publications
(161 reference statements)
0
3
0
Order By: Relevance
“…In the United Kingdom, research on Virginia Creeper (Parthenocissus quinquefolia) determined that this vine species delivers dynamic solar-shading benefits, adapting to seasonal shifts in climate and thus influencing external building temperatures (and adjacent microclimates) in summer and winter [42,65]. Virginia Creeper, sharing the deciduous growth cycle of the Boston Ivy analyzed in our research, is advantageous in the fluctuating temperatures typical of mid-latitude North American cities, ranging from sweltering sum-mers to frigid winters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United Kingdom, research on Virginia Creeper (Parthenocissus quinquefolia) determined that this vine species delivers dynamic solar-shading benefits, adapting to seasonal shifts in climate and thus influencing external building temperatures (and adjacent microclimates) in summer and winter [42,65]. Virginia Creeper, sharing the deciduous growth cycle of the Boston Ivy analyzed in our research, is advantageous in the fluctuating temperatures typical of mid-latitude North American cities, ranging from sweltering sum-mers to frigid winters.…”
Section: Discussionmentioning
confidence: 99%
“…Our examination of the literature and recent review articles summarizing green façade research has identified the need for standardized approaches to experimental design and measurement [65]. In combination with multidisciplinary teams, the ability to replicate green façade designs while varying underlying building materials and exposure to changing climatic conditions are necessary steps to shift toward a more widespread adoption of green façades as a component of UGI responses to climate warming.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the economic factor, one must consider the social, cultural, and environmental implications of contemporary architectural design [74], preferably employing as many locally sourced materials as possible to provide a comprehensive and sustainable approach towards the passive building. Vertical greenery systems or green façades on building envelopes could be considered to provide natural shade, cooling, insulation, and wind barrier benefits [75] in conjunction with a rooftop photovoltaic system to fully utilize the available local renewable energy to increase building energy efficiency [76].…”
Section: Discussionmentioning
confidence: 99%